Nestling sex and plumage color predict food allocation by barn swallow parents. (18th March 2016) - Romano, Andrea; Bazzi, Gaia; Caprioli, Manuela; Corti, Margherita; Costanzo, Alessandra; Rubolini, Diego; Saino, Nicola
Lay Summary: Barn swallow parents differentially allocated food to nestlings according to offspring plumage color and sex. In dyads of same-sex nestlings, males with experimentally darkened ventral plumage color obtained more food and gained more body mass than their sham-colored siblings, while such a biased favoritism did not occur among females. Because darker ventral color is associated with reproductive success in male barn swallows, the sex-related investment suggests an adaptive food allocation strategy by parents. Abstract: Despite parents are equally related to all of their progeny, they may differentially invest in offspring that provide the highest fitness return. Sons and daughters can differ in reproductive value, especially in species where fitness is predicted by the expression of sexually selected traits. In many birds, offspring plumage coloration functions as a honest signal of individual quality, thus allowing parents to differentially invest in offspring of either sex accordingly. Here, we tested whether parents allocate different amounts of food depending on plumage color of their male and female offspring. As a model, we used the barn swallow ( Hirundo rustica ), a species where large among- and within-brood variation in ventral plumage color exists and male reproductive success varies according to ventral plumage coloration. We recorded the proportion of feedings obtained and body mass variation by dyads of same-sex and similar-sized nestlings subjected to either experimental darkening of their ventral plumage color or to a sham treatment. Plumage darkening enhanced food provisioning and body mass gain of males but not of females. Because darker ventral coloration is associated with larger reproductive success in male barn swallows, these results suggest that parents tune their effort toward more valuable male offspring that are likely to provide the greatest fitness returns. Our study thus suggests that parents are selected to differentially invest in offspring of either sex according to a trait expressed in early life, which is relevant to intrasexual competition for access to mates at sexual maturity.